2017
DOI: 10.1038/cddis.2017.424
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of pancreatic tumorigenesis under immunosuppressive microenvironment induced by Reg3g overexpression

Abstract: Reg3g is a potential risk for pancreatic ductal adenocarcinoma (PDAC). We previously demonstrated that Reg3g promoted pancreatic carcinogenesis via a STAT3 signaling pathway in a murine model of chronic pancreatitis. Whether the immune response is involved in tumorigenesis induced by Reg3g remains unknown. In this study, Reg3g-regulated tumor immunity was evaluated in tumor-implanted murine models, immune cells, and tumor microenvironment. In mice that had been orthotopically or ectopically implanted with Panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Regenerating islet‐derived protein 3‐gamma (Reg3g) has been associated with colonic Paneth cell stemness and survival 28 . Two recent studies have revealed a novel immunosuppression role of Reg3g that weakens tumor‐specific antigenicity and suppresses antitumor effects of CD8+ T cells in murine models of pancreatic cancer, by activating the JAK2/STAT3 signaling pathway in DCs 29,30 . Lipocalin‐2/NGAL has been shown to be overexpressed in many solid cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerating islet‐derived protein 3‐gamma (Reg3g) has been associated with colonic Paneth cell stemness and survival 28 . Two recent studies have revealed a novel immunosuppression role of Reg3g that weakens tumor‐specific antigenicity and suppresses antitumor effects of CD8+ T cells in murine models of pancreatic cancer, by activating the JAK2/STAT3 signaling pathway in DCs 29,30 . Lipocalin‐2/NGAL has been shown to be overexpressed in many solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…28 Two recent studies have revealed a novel immunosuppression role of Reg3g that weakens tumor-specific antigenicity and suppresses antitumor effects of CD8+ T cells in murine models of pancreatic cancer, by activating the JAK2/STAT3 signaling pathway in DCs. 29,30 Lipocalin-2/NGAL has F I G U R E 3 Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) detection of mRNA of selected genes/ proteins normalized to β-actin for validation of proteomic and microarray platforms. Missing columns were due to either missing hybridization probes (microarray) or lack of protein detection sensitivity by iTRAQ proteomics.…”
Section: Validation Of Differential Expression Of Selected Genes Anmentioning
confidence: 99%
“…Based on our previous work, and that of other labs, DC dysfunction in tumors might be a consequence of soluble factors secreted by cancer cell into the TME. These soluble factors include Reg3 g, IL-6, and IL-10 in tumor-conditioned medium (Liu et al, 2017a;Wang et al, 2016). To elucidate whether tumor-conditioned medium suppressed BMDC maturation via elevated H3K79me2-FOXM1 expression, we conducted an in vivo experiment pretreating BMDCs from wild-type mice with conditioned medium from Panc02 or CT-26 cells, mimicking TME, before pulsing them with EPZ or Thiostrepton.…”
Section: Tumor-conditioned Medium Inhibited Bmdc Maturation Via H3k79mentioning
confidence: 99%
“…4A). Notably, several of these genes such as Vsig4, Deptor, Reg3g, Hgfac, and Cxcl13 encode proteins with previously identified roles in promoting tumor invasion and migration or influencing immune responses (22)(23)(24) or denote protumorigenic macrophage phenotypes such as Cd163 and Vsig4 (25,26).…”
Section: Alterations In Macrophage Populations Distinguish Prostate Cmentioning
confidence: 99%